Impact of the gamma variant on the icu admission in a hospital of the autonomous city of Buenos Aires (Caba), Argentina - Verónica Mandich; Daniel Chiacchiara; Antonio Pilipec; Santiago Grimaldi; Johnny Cotez; Víctor Paniouk; Oswaldo Escobar; Henry Arévalo; Sebastián Pérez Flach; Amílcar Herbas Pozo; Alejandro Aimar; Marcelo Bravo (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2021)
Objectives: Comparison between patients admitted to the Intensive Care Unit (ICU) with ventilatory support during the first and second wave (Gamma variant) of COVID 19 in a tertiary hospital in the City of Buenos Aires. Design: Descriptive, observational, prospective cohort study. Setting: ICU of an acute general hospital in Argentina. Patients: Adult patients with COVID-19 admitted consecutively to the ICU. Intervention: Admission to ICU. Main variables of interest: Demographic and laboratory data, history, duration of MV, mortality. Results: 44 patients were recruited during the first wave, and 80 in the second. Significant differences were observed in the second wave for age (60, [SD 11]; vs 68 [SD 11]; p <0.01), days with symptoms (9 [SD 5]; vs 4.5 [SD 3]; p <0.01), duration of MV (10 days [SD 7]; vs 16 [SD 13]; p <0.01), Ferritin (1450 mcg / l [SD 547]; vs 941 mcg / l [ SD 593]; p 0.04) and use of antibiotics (97% vs 45% p <0.01). There was no difference in mortality (66% vs 78% p 0.14) but there was in its primary causes; being more frequent hypoxemia associated with sepsis in the second wave (40% vs 3.4% p <0.01) and hypoxemia and multiorgan failure in the first (28% vs 4% p <0.01). Conclusions: During the second wave of the pandemic, due to Gamma variant, more patients were admitted to our unit, younger, with a longer evolution time, a shorter time on MV and a greater inflammatory response, with no difference in mortality, although there was a difference in its causes.